Going Green in the Education of Education of Future Managers - Huttmanová, Emília; Chovancová, Jana; Mikča, Radoslav (Publishing House of Wroclaw University of Economics and Business, 2024)
The need to move society towards more sustainable living patterns is now reflected in many strategic European and global documents. This urgency has arisen from the pressure that humanity exerted on the environment and its resources. Changes in production and consumption trends are now inevitable, but their implementation is neither easy nor quick. Implementing such profound structural changes across the economy also requires understanding and support from society. It requires a sophisticated society both aware of the need for such change and capable of managing this transformation. Educational systems, and in particular higher education, offer and co-create an enabling environment for learning about the changes underway (climatic, social, demographic, etc.), their dynamics, impacts and overlaps, in order to promote adaptation and resilience in society. Higher education has the potential to go far beyond the educational institution, and a suitably trained and profiled graduate can be a valuable resource and accelerator of progress for society. The aim of this paper was to present different ways of implementing current challenges and trends, with an emphasis on green topics, into the educational content of future managers, using the example of the Faculty of Management and Business, University of Prešov, Slovakia.
Huttmanová, E., Chovancová, J., & Mikča, R. (2024). Going Green in the Education of Future Managers. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 32-48). Publishing House of Wroclaw University of Economics and Business.
Keywords: education; green topics; future managers